4, 977‐bp human mitochondrial DNA deletion is associated with asthenozoospermic infertility in Jordan. (20th November 2019) - Al Zoubi, Mazhar S.; Al‐Batayneh, Khalid; Alsmadi, Mohammad; Rashed, Mitri; Al‐Trad, Bahaa; Al Khateeb, Wesam; Aljabali, Alaa; Otoum, Osama; Al‐Talib, Mohammad; Batiha, Osamah
Abstract: Male infertility is commonly associated with sperm abnormalities including asthenozoospermia. The molecular basis of asthenozoospermia was linked to mitochondrial DNA (mtDNA) mutations. The 4, 977‐bp human mtDNA deletion is one of the most common mutations of spermatozoa and results in loss of about 33% of the mitochondrial genome. In this preliminary study, we aimed to investigate the presence of 4, 977‐bp mtDNA deletion in asthenozoospermic infertile men in Jordan. Semen specimens of 120 asthenozoospermic infertile men and 80 normozoospermic individuals were collected at the in vitro fertilization unit. MtDNA was extracted after the enrichment of spermatozoa; then, polymerase chain reaction was performed using 4, 977‐bp mtDNA deletion‐specific primers. The deletion of 4, 977‐bp mtDNA was detected in 79.2% of asthenozoospermic patients compared to 10% in normozoospermic controls. The results showed a significant association between the presence of 4, 977‐bp mtDNA deletion and the asthenozoospermia and infertility (OR = 34.2000, 95% CI = 14.57–80.26, p ‐value < .001). In conclusion, our findings underscored a strong association between 4, 977‐bp mtDNA deletion and asthenozoospermia in the Jordanian population.